Comparative Study of the Effect of Lipo-6-Black and Caffeine on the Fertility of Male Albino Rats - Yasameen Shaker Mahmood; Mukhtar Khamis Haba (Institute of Medico-legal Publications Pvt Ltd, 2021)
This study was conducted to find out the effect of different doses of Lipo-6-black fat burner and Caffeine onthe physiology of parts of the reproductive system of white male rats. The experiment included administeringthe Lipo-6-black fat burner to male white rats orally at concentrations (16.82, 8.41 and 4.20). Mg / kg)for 3-6weeks , and also giving Caffeine orally, which is considered one of the main components of the fat burnerat concentrations (11.42, 5.71, and 2.85 mg / kg) for a period of 3-6 weeks for each concentration. Thestudy recorded the presence of weight changes of testis in addition to physiological changes, as it includedthe results of the first experiment were a decrease in in the weights of the testis and the levels of hormones(Testosterone, LH, FSH) at the middle and end of the experiment. As for the results of the second experiment,, changes in the weight of the testis , and an increase in the hormone levels themselves were observed at Themiddle of the experiment, while at the end of the experiment, no effect on hormones was shown.